Trump 101 - McIver, Meredith; Trump, Donald (Tantor Media, Inc., 2006)
An enlightening collection of business wisdom from the world's most famous dealmaker. Trumpisms is a collection of wisdom, pep talks, inspiration, and advice straight from the mouth of Trump himself. Organized around 20 distinct motivational themes-like "think big," "knowledge is power," "learn by doing," "go with your gut," and "don't do it for the money"-this enlightening collection of wisdom on business and life offers inspiration and motivation to businesspeople and entrepreneurs in any industry.